Development of Student Worksheets Oriented Guided Inquiry to Improve Student’s Critical Thinking Skills on Acid Base Material - Septia Nurkhalida; Harun Nasrudin (UNIB Press, 2023)
This research aimed to obtain the validity, practicality, and effectiveness of student worksheets oriented on guided inquiry to improve critical thinking skills in acid-base material. The type of research used was 4D model development research, but it was limited to the third stage, namely Develop. The research sample consisted of 34 students from class XI IPA 4 SMAN 14 Surabaya. The instruments used were validation sheets, student response questionnaires, and pretest and posttest question sheets. The validation results show that the student worksheets 1, 2, and 3 in the content criteria get mode 4 in the good category, and construct criteria get mode 5 in the very good category so that overall the teaching module gets mode ≥3 and is declared valid. The overall practicality results of the student worksheets obtained an average percentage of 90.09% with efficient criteria. The results of the overall effectiveness of student worksheets oriented on guided inquiry obtained an n-gain score of 0.71 which is included in the high category. In addition, the sig value. (2-tailed) obtained from the paired sample t-test of 0.000 which shows an increase in students' critical thinking skills and the student worksheets oriented on guided inquiry are effective for use in learning.